Examination of products of conception terminated after prenatal investigation. Issue 10 (October 1986) - Knowles, S
Abstract : A large number of district general hospitals have access to diagnostic ultrasonography and other methods of prenatal diagnosis, resulting in an increased supply of freshly terminated malformed fetuses to general histopathology departments, and there is now more open discussion of malformation and greater concern over fetal wastage. General pathologists are therefore under greater pressure to produce complete and detailed descriptions of a wide range of often complex anomalies. The dismissal of specimens as "multiple congenital anomalies" is becoming increasingly unacceptable to couples who wish to embark on further pregnancies and to their medical attendants. As in other fields an understanding of the methods and terminology in clinical use and a consistent diagnostic approach should help pathologists to extract sufficient information for accurate counselling.